Laparoscopic Approach to a Case of Appendicular Schwannoma - Suh, Suk Won (The Korean Society of Coloproctology, 2010)
Appendicular schwannoma is a rare tumor originating from Schwann's cells in the Auerbach plexus. The preoperative diagnosis is difficult because the clinical features are nonspecific, and it is mostly found accidentally via a radiologic image as a tumor, mimicking malignancy. We report a case of an appendicular schwannoma coexisting with an adenocarcinoma in the lung. A laparoscopic appendectomy was done with a clear resection margin, and the immunohistochemical staining showed positive S-100 protein, which confirmed the schwannoma. The patient also underwent a left upper lobectomy of the lung. The patient has been free of recurrence for the 6 months since the operation. The laparoscopic approach could be available for treatment of an appendicular schwannoma, thus avoiding an unnecessary laparotomy.